End-of-Life Care in a General Respiratory Ward in the United Kingdom. (March 2014) - Tsim, Selina; Davidson, Scott
Introduction: Patients with advanced chronic lung disease such as chronic obstructive pulmonary disease (COPD) often have an unpredictable clinical course and a high symptom burden. Their prognosis is similar to that of patients with lung cancer. Aim and Methods: We retrospectively assessed end of life care in all patients who were admitted and subsequently died on a general respiratory ward in a central teaching hospital over a period of 11months (1st June 2010-1st May 2011). We compared our practice with guidelines set out in Living and Dying Well, a national action plan for palliative and end of life care in Scotland. Results: There were 66 deaths, data was obtained for 57 patients (86.4%). Patients with lung cancer had higher rates of recorded discussions regarding their prognosis in comparison to those with COPD (60%, n=9 vs. 8.3%, n=1 respectively). In addition, they had greater levels of in-patient palliative care involvement (50%, n= 7 vs. 0% respectively) and higher rates of recorded wishes end of life care destination (28.6%, n=4 vs. 8.3%, n=1 respectively). This is despite patients with lung cancer having a lower mean number of end of life clinical indicators (2.64 vs. 3.17 respectively) and a lower mean number of admissions in the 12months preceding death (1.67 vs. 4.08). Conclusions: Palliative care involvement and discussion of patients' end of life care wishes is poor in COPD. Timely and effective discussions regarding disease prognosis and patient wishes, including early consideration for initiating anticipatory care planning needs to be instituted.